An updated review on primary signet-ring cell carcinoma of the urinary bladder and report of a case. (4th March 2018) - Lendorf, Maria Elisabeth; Dohn, Line Hammer; Á Dunga, Bara; Loya, Anand C.; Pappot, Helle
Abstract: Objective: The aim of the present study was to emphasize the critical importance of the clinician's awareness of signet-ring cell carcinoma (SRCC) of the urinary bladder, a rare and aggressive disease entity. Materials and methods: A review of the current literature was conducted and a classic case of advanced SRCC of the urinary bladder is reported, clearly demonstrating the severity of this disease and the imperative need for standardized recommendations for the diagnostic work-up and management of urinary bladder SRCC. Results: The prognosis for patients with SRCC of the urinary bladder is poor, attributed to presentation at advanced stages following asymptomatic progression, inefficacy of multimodality therapy and possibly an aggressive underlying biological phenotype. Treatment options are limited and not well studied. Conclusion: Given the rarity of SRCC, multi-institutional clinical trials and international cooperation are mandatory to improve survival for patients with primary SRCC of the bladder.